Intraoperative fluid management guided by oesophageal Doppler monitoring. (24th May 2011) - Kuper, Martin; Gold, Stuart J; Callow, Colin; Quraishi, Tanviha; King, Sarah; Mulreany, Aundrea; Bianchi, Michele; Conway, Daniel H
Abstract : Problem Fluid management during major surgery poses a challenge to the surgical team as postoperative complications are often related to giving the wrong amount of intravenous fluid. Postoperative morbidity can be reduced by using the oesophageal Doppler cardiac output monitor to individualise fluid administration, but this technology has not been widely adopted. Design A campaign for adopting this technology in major surgical specialties explored clinical and managerial barriers throughout the procurement and implementation process. We compared patient outcomes 12 months before implementation and after implementation. Setting Three large hospitals in England with different size, geographical location, and case mix. Strategies for change Project leads at each site included a consultant anaesthetist, a divisional manager, and an audit facilitator. A business case was prepared by each team with support from NHS Technology Adoption Centre, allowing senior management to overcome the unequal spread of costs versus benefits. A survey of anaesthetists revealed concerns about familiarity with the device, which we dealt with by clinicians volunteering to "champion" the technique, supported by standard training provided by the manufacturer. We encouraged appropriate use of the technology by collecting intraoperative patient related data and postoperative patient outcomes and by giving regular, timely feedback. Key measures for improvement The key outcome measure was length of hospital stay. In-hospital mortality, readmission, and reoperation rates were also recorded. Process measures were use of monitors and change in stroke volume during surgery. Effects of the change We compared 649 patients after implementation across all sites with 658 matched cases before implementation. Use of Doppler increased from 11% to 65% of eligible operations, with a 3.7 day reduction in total length of stay. Length of stay was reduced at each site, and in most specialties. Concurrent improvements in patient care could have contributed to these findings. The only sign of harm from the intervention was one episode of pulmonary oedema. Mortality, readmission, and reoperation rates all fell non-significantly. Lessons learnt Managerial barriers consisted of silo budgeting, difficulties with preparing a business case, and fears about uncontrolled implementation. By collecting outcome data, we convinced senior managers to support and sustain investment. Clinical barriers consisted mainly of scepticism regarding clinical effectiveness and worries about training. Clinicians "championing" the technology took on responsibility for data collection, education, advocacy, and spanning boundaries. When barriers to adoption of oesophageal Doppler monitoring are overcome, outcome improvements suggested by research can be replicated in the real world. The project generated a web based guide (www.howtowhyto.nhs.uk ) to provide tools and resources to support implementation.